Disruption or Transformation? Australian Policymaking in the Face of Indigenous Contestation - Tanja Dreher; Lisa Waller; Kerry McCallum (2018)
From the Zapatista’s “netwar” to the “hashtag activism” of Idle No More, Indigenous peoples have pioneered digital media for global connectivity and contestation. This chapter explores the promise and the pitfalls of social media for First Nations protest in Australia. Overall, we find new opportunities for disruption and ongoing challenges with regard to significant social and political transformation. The argument is illustrated with two exemplars. Firstly, the “Recognise” campaign is a state-sponsored public information and awareness campaign with a well-developed social media and branding strategy. Dissenting Indigenous voices have been highly successful in disrupting this campaign and asserting an alternative agenda including Treaty and Land Rights. Secondly, the #IASLottery campaign responded to the new Indigenous Advancement Strategy, with less success in impacting policy debates.